Effectiveness of Education Through Digital Media to Improve Clean and Healthy Living Behavior (PHBS) Skills in Guidance Center Students in Malaysia - Maesaroh Lubis; Neni Nuraeni; Lilis Lismayanti; Mujiarto Mujiarto; Elfan Fanhas Fatwa Khomaeny; Asep Setiawan; Miftahul Falah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Digital transformation in health education opens up innovative opportunities to improve clean and healthy living behavior skills in the adolescent population. This study aims to analyze the effectiveness of education through digital media in improving clean and healthy living behavior skills in guidance studio students in Malaysia. The research method uses a mixed-method approach with a participatory action research design that integrates cooperative learning as the main strategy. The subjects of the study involved 32 students of Sanggar Bimbingan Kampung Pandan Malaysia consisting of 18 male students and 14 female students with an age range of 12-16 years. The intervention was carried out for 12 weeks using the